AN EFFECTIVE TREATMENT FOR PATIENTS WITH KNEE OSTEOARTHRITIS: INTRA- ARTICULER SODIUM HYALURONATE INJECTIONS COMBINED WITH HOME EXERCISE PROGRAM - Murat Ersöz; Şenay Kahramanlar; İnci Yanıkoğlu and Feray Kızıltepe (Archives of Rheumatology, 2001)
The purpose of this study was to compare the changes of clinical and functional parameters in intraarticular sodium hyaluronate injected knee osteoarthritis (OA) patient group and in injection plus home exercise program group. Twenty-three patients with knee osteoarthritis who fulfilled the clinical and radiological criteria of American College of Rheumatology (ACR) for OA were investigated (mean age: 59.52 + 8.56 (43-80), 6 male, 17 female). Thirteen randomly selected patients were given a home exercise program in addition to intra-articular injections. Home exercise program included isometric quadriceps exercises and straight leg rising while knee extended. The groups were similar in respect to demographic, clinical and functional parameters. All patients were reevaluated in the week following third injection. Weight-bearing pain, rest pain and night pain levels decreased significantly in both groups. The patientÕs impression was rated as “better” or “much better” in 80% of injection group patients and % 84.6% of injection plus exercise group patients. There were significant improvements in 20 m. walking time, time to walk up and down one flight of stairs and time to rise from chair and sit down again for three times in injection plus exercise group. The improvements were not statistically significant in injection alone group. Intra-articular sodium hyaluronate injections combined with home exercise program improved clinical and functional parameters rapidly in knee osteoarthritis patients. This combination therapy seems to be an effective choice of treatment in this patient group.